Nature of female alcohol addiction - Chuchra, Maria (Current Problems of Psychiatry, 2012)
Female alcohol addiction is a phenomenon that has continued to intensify. It is connected to various social and cultural as well as economic processes, especially those regarding the change to the positions and roles played by women in society and in the family. The factors to enhance the risk of alcohol abuse and dependence in women include genetic load, early initiation of alcohol consumption and victimisation. The article presents biological, psychological as well as social and cultural differences between the alcoholism in women and men, the consequences of drinking in women and the specificity of their therapy.